2011
DOI: 10.1097/yco.0b013e3283453775
|View full text |Cite
|
Sign up to set email alerts
|

Brain dysfunction in anorexia nervosa: cause or consequence of under-nutrition?

Abstract: The elucidation of the neurobiology of anorexia nervosa has benefited from recent advances in neuro-imaging and cognitive neuroscience. Further research is needed to examine the degree to which abnormalities are a consequence of starvation or are caused by a putative anorexia nervosa endophenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…This suggests that previous findings which highlight differences in subjective embodiment in relation to eating disorder psychopathology may be body part specific 36,38,74 . Nevertheless, studying eating disorder characteristics within healthy individuals remains clinically important to identify factors associated with the development of eating disorders without the confounds of physical consequences of the disorder 75,76 .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that previous findings which highlight differences in subjective embodiment in relation to eating disorder psychopathology may be body part specific 36,38,74 . Nevertheless, studying eating disorder characteristics within healthy individuals remains clinically important to identify factors associated with the development of eating disorders without the confounds of physical consequences of the disorder 75,76 .…”
Section: Discussionmentioning
confidence: 99%
“…First, deficits in general cognitive functioning caused by extreme starvation can confound measurements of FER in acute AN (Hay & Sachdev, 2011;Kaye, Fudge, & Paulus, 2009). Whether FER deficits are limited to the starvation phase or extend beyond recovery is an important question to answer to better understand the role of socioemotional difficulties in AN maintenance.…”
Section: Schultementioning
confidence: 99%
“…Previous research studies have also revealed cognitive deficits in patients with AN (Allen et al., ; Weider, Indredavik, Lydersen, & Hestad, ). Although the results of previous studies have not been entirely consistent, the available data indicate that some cognitive deficits are the consequence of starvation (Hay & Sachdev, ; Kaye, Fudge, & Paulus, ) and can be normalised with weight restoration (Hatch et al., ), particularly in adolescents (Buehren et al., ). However, other cognitive deficits may persist after recovery from AN, such as memory and executive function in particular (e.g.…”
Section: Introductionmentioning
confidence: 96%